2016
DOI: 10.1002/jemt.22747
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and distribution of antennal sensilla of two tortricid moths,Cydia pomonellaandC. succedana(Lepidoptera)

Abstract: Morphology of antennal sensilla and their distributions were investigated in male and female adults of two tortricid moths, Cydia pomonella and C. succedana using scanning electron microscopy. The antennae of both sexes of the two species were filiform, and the overall lengths of the antennae and the number of consisting segments were greater in males than in females. Six types of sensilla (s.) were identified from the antennae of both sexes in the two species: s. trichodea, s. basiconica, s. coeloconica, s. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
9
18
0
Order By: Relevance
“…It has been suggested that the wall‐pores and longitudinal grooves are the entry points of odor molecules into the sensillum lumen (Maitani, Allara, Park, Lee, & Baker, ; Shields & Hildebrand, ; Steinbrecht, ; Zacharuk, ). Our study indicated that multiple nanoscale wall‐pores are present in trichoid and basiconic sensilla of male and female B. depressa , suggesting that their sensory function is olfactory, as demonstrated in other dipteran species such as P. tricuspis (Chen & Fadamiro, ), P. terraenovae (Setzu et al, ), and Stomoxys calcitrans (Muscidae; Tangtrakulwanich et al, ) as well as in other groups of insects (Roh et al, ; Wee et al, ). Extracellular recordings from coeloconic sensilla in some insect species have shown that their main function is olfactory (Hallberg et al, ; Pophof, ; Pophof et al, ; Yao et al, ), therefore, the main function of the coeloconic sensilla in the antennae of B. depressa is suggested to be olfactory.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…It has been suggested that the wall‐pores and longitudinal grooves are the entry points of odor molecules into the sensillum lumen (Maitani, Allara, Park, Lee, & Baker, ; Shields & Hildebrand, ; Steinbrecht, ; Zacharuk, ). Our study indicated that multiple nanoscale wall‐pores are present in trichoid and basiconic sensilla of male and female B. depressa , suggesting that their sensory function is olfactory, as demonstrated in other dipteran species such as P. tricuspis (Chen & Fadamiro, ), P. terraenovae (Setzu et al, ), and Stomoxys calcitrans (Muscidae; Tangtrakulwanich et al, ) as well as in other groups of insects (Roh et al, ; Wee et al, ). Extracellular recordings from coeloconic sensilla in some insect species have shown that their main function is olfactory (Hallberg et al, ; Pophof, ; Pophof et al, ; Yao et al, ), therefore, the main function of the coeloconic sensilla in the antennae of B. depressa is suggested to be olfactory.…”
Section: Discussionsupporting
confidence: 70%
“…Despite diverse external morphology, the olfactory sensilla in insects usually share a common feature containing multiple nanoscale wall‐pores (Kim et al, ; Onagbola & Fadamiro, ; Roh et al, ; Wee, Oh, & Park, ). An exception is coeloconic sensilla, which exhibit longitudinal grooves instead of multiple wall‐pores (Diongue, Yang, & Lai, ; Faucheux, Kristensen, & Yen, ; Roh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antennae are the major olfactory sensory organ in insects, housing various types of olfactory sensilla of which olfactory function can be morphologically characterized as having multiple cuticular pores (Chen & Fadamiro, ; J. Kim et al, ; Onagbola & Fadamiro, ; Roh, Park, Oh, & Park., ; Setzu, Poddighe, & Angioy, ; Wee, Oh, & Park, ; Zacharuk, ). Pheromones and other semiochemicals are mainly detected by the olfactory sensilla in the antennae of insects (Baker et al, ; Larsson, Leal, & Hansson, ).…”
Section: Introductionmentioning
confidence: 99%